Impacts of Light Rail Transit Tram on the Voltage and Unbalance of the Distribution System. (18th November 2013) - Hsu, Cheng-Ting; Huang, Hung-Ming; Cheng, Tsun-Jen; Tsai, Lian-Jou
Abstract : This paper presents the three-phase voltage and unbalance analysis for the distribution system with the loading of a light rail transit (LRT) tram. To investigate the dynamic responses of the system voltage and current, this paper adopts the Alternative Transients Program (ATP) software to model and simulate a multigrounded four-wire distribution system with an LRT loading. Two different definitions about unbalance are used to evaluate the problem. In this paper, the traction supply substation (TSS) with a single-phase transformer configuration is designed first for providing the electric power to the trams of LRT. However, it may result in the significant neutral line current and unbalance phenomenon to deteriorate the power quality of the distribution system. A Le-Blanc connection transformer in the TSS is therefore proposed to solve the problems.